Prediction of Power Generation Performance of Wound Rotor Synchronous Generator Using Nonlinear Magnetic Equivalent Circuit Method - Hyo-Seob Shin; Do-Yun Kwon; Jong-Hyeon Woo; Hoon-Ki Lee; Jang-Yong Choi (Energies, 2021)
This paper presents a nonlinear magnetic equivalent circuit method and an electromagnetic characteristic analysis and verification of a wound rotor synchronous generator (WRSG). The reluctance generated by the stator, rotor, and air gap is subdivided to form a reluctance construction. A nonlinear magnetic equivalent circuit (MEC) for the WRSG is constructed and solved by an iteration method. Moreover, to calculate the inductance of the generator, the reluctance circuit of the <semantics>d−q</semantics>axis is constructed, and the inductance of the generator is obtained using the initial relative permeability of the material. Using the electromagnetic parameters obtained via the MEC method, the power generation characteristics of the generator are predicted. The results of this MEC method are also verified by comparing them with the finite element analysis (FEA) results and experimental results.